Utilizando recursos audiovisuais como mediadores para ensinar a Teoria do Big Bang à luz da história e filosofia da ciência - Carapiá, Dilton Lopes (2016)
Even with all the technological advances provided by science in recent centuries, there is still little approach of Modern and Contemporary Physics (MCP) knowledge objects in basic education schools. Aiming at contributing to a change in this scenario, we produce and applied a Didactic Sequence (DS), supported by the learning theory of Lev Vygotsky, to teachthe theory of the Big Bang in the light of History and Philosophy of Science (HPC). Using audio-visual resources, in the process of mediation, as well as historical and philosophical contextualization, we seek the motivation needed to give meaning to the signs that we aim to internalize. Topics such as the Special and General Relativity (SGR), appear as stages of the evolution of human thought and corroborate changes in the way of seeing and interpreting the world.